Begavî tefsirinde kıraat olgusu - Saylan, Nesrişah (My University, 2018)
Bu çalışmanın amacı, V/XII. yüzyıl âlimlerinden olan Begavî’nin Me‘âlimu’t-Tenzîl adlı tefsirinde esas aldığı kıraat anlayışını ve kıraatleri kullanma keyfiyetini ortaya koymaktır. Begavî’nin tefsiri her ne kadar kıraat ilmine dair bir eser olmasa da, Kur’ân’ın okunuşu ile ilgili pek çok kıraat farklılığını içermektedir. Ayrıca kıraat tarihinde on’lu sistemin (kıraat-i aşere) yerleşmesinde önemli bir role sahip olan Begavî, kıraat ilmine dair müstakil bir eser kaleme almıştır. Biyografik kaynakların çoğunda Begavî’den “mukrî” olarak da bahsedilmektedir. Bu özellikleri sebebiyle kıraat ilminde önemli bir konuma sahip olan Begavî’nin bakış açısıyla kıraatlerin nasıl ele alındığı ve değerlendirildiği önem arz etmektedir.

The aim of this study is to present understanding of the recitation and the determination of the using arbitrariness of recitation in the 5th and 12th century scholar al-Baghaw?'s interpretation called Me‘?limu’tTenz?l. Although al-Baghaw?'s commentary is not a work of recitation science, it includes lots of differences of the recitation in the readings of the Qur’?n. Moreover, al-Baghaw? who had an important role in the settlement of the system of ten (Reading ten of the recitation sciences) in the history of recitation, has received an specific piece of work related to the recitation science. Biographical sources are referred to as “reader” by himself. Because of these features, it is important to see how the cherries are handled and evaluated by al-Baghaw? who is an important personal figure in the recitation.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Kur’ân; Tefsir; Kıraat; Kıraat-i Aşere; Begavî; Qur’?n; Interpretation; Recitation; Reading ten of the recitation sciences; al-Baghaw?